ArUco Marker-Based autonomous UAV navigation for reconnaissance operations in urban terrain environments - Cahya Pradika; Imanuel Dindin; Erzi Agson Gani; Ardan Nagra Coutsar; Mochamad Riza Pratama (Journal of Automotive and Mechanical Applied Technology, 2026)
This study demonstrated the feasibility of autonomous UAV navigation in GPS-denied indoor environments using ArUco marker-based visual localization integrated with a VL53L1X LiDAR sensor and PX4 Offboard control. The developed system successfully validated markers, performed real-time pose estimation, and navigated sequentially through waypoints without human intervention. The web-based monitoring interface and QGroundControl integration operated reliably throughout all trials, enabling effective dual-platform telemetry monitoring and manual setpoint adjustment from a safe standoff position. The ArUco-marker-based detection, implemented using the OpenCV DICT_5×5_250 dictionary, validated marker identities within a functional altitude range of 40 to 200 cm. Third, across 61 trials discrete movement samples spanning four path configurations—straight-axis, lateral-right, lateral-left, and compound multi-direction—the system achieved an overall navigation success rate of 70%. Navigation failures caused by synchronization lag between UAV translational velocity and the camera’s image processing frame rate, which prevented timely marker validation during high-speed maneuvers. These results confirm that ArUco marker-guided UAV navigation is a viable, low-infrastructure solution for initial indoor reconnaissance in GPS-denied military environments, and establish a quantitative baseline for future enhancements, including precision landing algorithms and dynamic marker placement strategies.